2021
DOI: 10.3946/kjme.2021.210
|View full text |Cite
|
Sign up to set email alerts
|

Delivering a modified continuous objective structured clinical examination for ophthalmology residents through a hybrid online method

Abstract: Since coronavirus disease 2019 was declared a global pandemic by the World Health Organization, it has become a challenging situation to continue medical education, including in Indonesia. The situation prohibited face-to-face (direct) educational activities in clinical settings, therefore also postponing examinations involving especially procedural skills. Adaptations were urgently needed to maintain the delivery of high-stake examinations to sustain the number of ophthalmology graduates and the continuation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…All but 10 studies reported assessment within a single institution. The remaining 10 were either board examinations or national (Objective Structured Clinical Examination) OSCEs of different countries 18–27 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All but 10 studies reported assessment within a single institution. The remaining 10 were either board examinations or national (Objective Structured Clinical Examination) OSCEs of different countries 18–27 …”
Section: Resultsmentioning
confidence: 99%
“…Of the 44 articles reporting practical assessment, 32 were conducted online, 16,24,25,34,37,38,49,51–58,62,64–71,75–82 4 were conducted in person 36,59,60,63 and 8 used a hybrid format of assessment 17,21,23,26,61,72–74 . Several competencies such as professionalism, clinical reasoning and history‐taking were assessed using OSCE; however, none of the OSCE conducted online could assess hands‐on skills.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 pandemic when in-person OSCE assessments were not possible, many health professional schools rapidly implemented online OSCEs as a substitute ( Hytönen et al, 2021 ; Jamil et al, 2022 ; Luke et al, 2021 ; Nusanti et al, 2021 ). While online OSCEs are modeled after in-person ones, the online format itself is a major change, and the number of stations or competencies tested may be altered; therefore, its validity and reliability are uncertain.…”
Section: Introductionmentioning
confidence: 99%
“… 96 Due to the COVID-19 pandemic, many face-to-face OSCEs were converted to an online or hybrid format. 97 , 98 , 99 , 100 , 101 Experiences from Nurse Practitioner students 102 were positive and it highlighted that the interactive Virtual OSCE was deemed an extremely effective tool for virtual evaluation of various clinical competencies. Similar positive findings were also echoed by Farrell et al.…”
Section: Introductionmentioning
confidence: 99%